(3JfhjQ GdOjGLi aj JaSjQ GdCMGLis - (3Yde GdOjf CHi GdMSf Ydj Hf eMeO YHO GdUeO GdSNGhis; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3eMMeO Hf CHj GdRgQ Hf eYGdi GHf YScQ GdCfUGQi s)
(3ChdgG (B:s
(3GdMeO ddg GHJOGA HPcQg hGfJgGA Edi CeQg hGSJjaGA dfYeg HTcQg hbO QCjJ Cf CTQM GdCMGLi GdJi hVYgG YdGeI ReGfg hUjGHg ChGfg CHh GdbGSe GdReNTQi hCf ChVM ZGeVgG HGdJaSjQ GdLdi hCf CLYd Pdc s
(3BNQgG (B:s
(3hdjS gPG ef bHjd eG ai gPG GdcJGH , aGf ajg ef GdeSGFd hGdahGFO eGdGjhLO eLehYG ai cJGH heGdGjJgjC ajg dhdG cTag LhGH hMSHfG Gddg hfYe Gdhcjd s
(3GfXQ GdLRA GdChd HQbe (B160 (3COHs
(3hgh TQM GdCMGLi GdJi hVYgG LGQ Gddg eMehO Hf YeQ GdReNTQi GdeJhai (B538(3g`s
(3hbO GdJRe GdSNGhi ai TQMg hJaSjQg Cf jYbH cd CMLjI ddReNTQi HdZRjf ef fXegs
(3hbHdgG JbQjX ddcJGH SfI (B641s
(3hHHYV ChQGbgG JbWY s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs